Identifikasi Sosial Ekonomi Wilayah Rencana Pembangunan Jembatan Selat Sunda - Dewi, Enfy Diana (Jurnal Sosial Ekonomi Pekerjaan Umum, 2009)
Sunda Strait Bridge as part of the Trans Asia, is expected to accelerate equitable economic aspects of development, especially between the island of Sumatera and Java. This grand plan will create not only positive impacts but also negative effects. To have negative impacts that may arise can be anticipated and the positive impact can be maximized, this study was to explore the potential economic and social problems as result of the Sunda Strait Bridge construction, using qualitative and quantitative analysis. The results of this study indicate there are still many things to be prepared by all relevant stakeholders, especially Local Government in Sumatera to set policies and infrastructures. Otherwise, Sunda Strait Bridge will only deepen the economic gap between Java and Sumatera.